ROBLOX ROLE-PLAY MEDIA DEVELOPMENT TO IMPROVE PRACTICAL SKILLS OF HAJJ UMRAH MANASIK AT MTSN 1 TUBAN - Abdul Khamid Nasimul Askhia; Isnawati Nur Afifah Latif (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
A Roblox-based role-play learning medium was developed to support the teaching of Hajj and Umrah practice materials at MTsN 1 Tuban. The development process applied a Research and Development approach using the ADDIE model. The product trial involved 34 eighth-grade students and employed a one-group pretest-posttest design. The data were obtained through expert validation sheets, teacher and student response questionnaires, classroom observation, and performance-based assessment. Expert appraisal indicated that the media achieved a score of 90% from the material expert and 94% from the media expert, placing it in the highly valid category. In terms of practicality, the teacher response reached 90%, while the student response reached 87%, indicating that the media was easy to use in the learning process. The improvement in students’ practical skills was reflected in the increase of the average pre-test score from 60 to 90 in the post-test, with an N-Gain score of 0.75 in the high category. These findings indicate that Roblox-based role-play media is feasible as an alternative tool for Islamic jurisprudence learning, particularly in helping students understand the stages of Hajj and Umrah practices in a more visual, interactive, and procedural way.